Capacitação de enfermeiros para o monitoramento de pacientes com doenças crônicas não transmissíveis - Silveira, Rafael Silva Martins (2015)
In the search for health promotion and prevention of the behaviors that affect the quality of life of the population, telemedicine has been used in Brazil and in the world as a resource to monitor and stimulate the health of people, who have chronic non-transmittable diseases. The aim of the present study was to contribute to telemedicine practice, by building, applying, and analyzing the results of a training program for nurses, who work with distance monitoring of people affected by one or more non-transmittable chronic diseases. Six nurses participated in the study. The training consisted of the following stages: the reading of a handout with information on the behaviors, which are considered relevant and appropriate to the monitoring process; short presentation to the group of participants regarding the central aspects of the handout, following by clarification of their doubts; five individual training sessions, being three of them related solely to the monitoring training, one related to both monitoring training and computer system registration of the main information regarding the monitoring; and a last session focused solely on computer system registration training. During the training sessions, the monitoring practices, which were performed by the nurses and transcribed by the researcher, were discussed using differential reinforcement of the participants responses, removal of the tips, and elaboration of the instructions, to achieve the proposed behavioral objectives. It was observed that, for the majority of the participants, increases in the occurrence of most of the trained behaviors, such as stimulating the patient to discuss about the aggravating factors and health protection, as well as the consequent specific-patient verbalization. For the behaviors of establishing the patients health care goals and complimenting them for their health care at the end of the monitoring practice, more time and different strategies would be needed to observe increase number of these occurrences. It was also observed that by verbalizing which behaviors were adequate, which were inadequate, and pointing out that no longer occurred, did not ensure the occurrence of appropriate behaviors in the subsequent monitoring training nor that inappropriate behavior no longer occurs. Finally, the training described in this work and its results showed that the principles proposed by Behavior Analysis applied to the development of the educational program could help to improve the verbal behaviors of the nurses during monitoring health of people with chronic non-transmittable diseases